Sejarah Etnis Tionghoa Dalam Dinamika Sosial Masyarakat Pulau Buru - Pattiasina, Johan (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2021)
The people who inhabit the island of Buru come from various places; among them, some groupings differentiate from one another and are known as Rana people, Wakahallo people, Orangakang, Earth lale people and traders. Of the five designations, this study focuses on "Trading People". In this case, the Chinese community. They also play an essential role in various community life sectors on Buru Island. Their existence is identified through names such as "Chinese Namlea, Chinese Namrole, Chinese Waplau and Chinese Buru". The purpose of this research is to explore the history of the arrival of the Chinese community on Buru Island and to identify the dynamics of Chinese life in terms of social, economic, political, and cultural aspects of Buru Island. To achieve this goal, the historical method was used in four stages: heuristics, verification, interpretation, and historiography. The number of Chinese communities on Buru Island is large and spread over several locations in several sub-districts. They live side by side with the local population without a barrier in the form of a high wall to separate them from the surrounding community. Their livelihoods generally are trading groceries and necessities and building materials for houses. In addition, they can also take advantage of the availability of natural resources on the island of Buru, namely eucalyptus oil and make it an important trading commodity with high economic value. Even though they have adhered to Christianity and Islam, they still maintain the Chinese tradition from their ancestors. Besides the trade sector, Chinese people in Buru have played an essential role in politics.